Fabrication of Cement Sand Brick (CSB) using aluminium dross as partial sand replacement - Ong, Zhe Yang (2022)
Globalisation and rapid development have increased the world's human population, stimulating development projects in the construction sector. Rapid construction activities increase the brick demand, leading to the mass production of brick. Firing brick contributes a lot of carbon footprint to the air and consumes lots of energy. The CO2 emission is causing climate change, threatening all the living organisms on Earth. Later, a more environmentally friendly non-fired brick, cement sand brick (CSB) is introduced to replace the use of conventional brick. However, the huge demand for CSB created another issue: the sand shortage. Increase in sand mining activities worldwide to solve the shortage problem and neglect the impacts of sand mining activities on the environment. Aluminium dross is a by-product of the aluminium industry. It exhibits hazardous characteristics because of the hydrolysed of aluminium nitride (AlN). Hence, incorporating AD is an effective solution to recycling hazardous AD while addressing the sand shortage and its impacts on the environment. The sand replacement percentage for this research ranged from 0 to 25 % of AD based on the requirement by DOE. All the CSB specimens were tested at 28 days of age to evaluate their engineering properties through bulk density, compressive strength, flexural strength, water absorption, porosity, microstructure analysis, and metal ions leaching test. In this research, the 20R specimen has the most optimum sand replacement percentage, as it fulfills the compressive strength, flexural strength, water absorption rate, bulk density, and leachability of metal ions stated in the standard. 20R specimen can reduce 29.44% of CO2 emissions from sand mining and cost 36.71% lower than the selling price of CSB in the market after the AD treatment. Thus, treatment of AD before substituting AD into CSB is feasible to be implemented.